Lifestyle psychiatry for depression and anxiety: Beyond diet and exercise - Madison C. Piotrowski; Julia Lunsford; Bradley N. Gaynes (Lifestyle Medicine, 2021)
Abstract There are a range of lifestyle factors which can negatively affect both a person's physical and mental health, and there is increasing evidence that therapeutic lifestyle change can be useful for the prevention and treatment of depression and anxiety disorders. The six core features of lifestyle medicine—regular physical activity, a whole food and plant predominant diet, restorative sleep, stress management, avoidance of substance abuse, and positive social connection—are important foci for mental health providers trying to help patients make meaningful lifestyle changes to improve their well‐being. Alongside these elements, there are likely many other aspects of lifestyle important to mental health. The aim of this paper is to provide an overview of five potential lifestyle targets which may play a role in the development and treatment of depression and anxiety, including financial stability, time in nature, pet ownership, materialistic values, and the use of social media. The paper will explore the evidence that these factors contribute to the burden of depression and anxiety in the modern world and will review the potential mechanisms of these effects and clinical implications of interventions targeting these factors.